Pre‐Programmed Rod‐Shaped Microgels to Create Multi‐Directional Anisogels for 3D Tissue Engineering. (1st September 2022) - Braunmiller, Dominik L.; Babu, Susan; Gehlen, David B.; Seuß, Maximilian; Haraszti, Tamás; Falkenstein, Andreas; Eigen, Julian; De Laporte, Laura; Crassous, Jérôme J.
Abstract: Micron‐scale anisometric microgels have received increasing attention to replace macromolecule solutions to create injectable 3D regenerative hydrogels. Interlinking these rod‐shaped microgels results in microporous constructs, while incorporating magnetic nanoparticles inside the microgels enables their alignment to introduce directionality. This report demonstrates that the angle of microgel alignment in a static external magnetic field can be pre‐programmed, broadening their applicability to artificially assemble into specific architectures. The magnetic rod‐shaped polyethylene glycol microgels are prepared via in mold polymerization. Ellipsoidal maghemite nanoparticles, integrated as responsive fillers are pre‐aligned either parallel or orthogonal to the long axis of the microgel with a weak magnetic field during rod fabrication to implement additional control over their magnetic orientation and allow their precise manipulation and actuation. The magnetic response of the microgels to static and rotating magnetic fields is discussed depending on various process and design parameters, such as magnetic field strength, angular frequency, and pre‐alignment. Finally, the applicability of the approach for tissue engineering is highlighted by growing mouse fibroblasts in three dimensions within Anisogels, i. e., hydrogels containing a mixture of rods with both a parallel and orthogonal orientation, marking a new step toward more advanced functional cell templating for tissue engineering. Abstract : Magnetic micrometric rod‐shaped microgels prepared via in mold polymerization are magnetically pre‐programmed using pre‐aligned anisometric maghemite as fillers. Depending on pre‐alignment conditions, the microgel rods can either align parallel or perpendicular to the applied magnetic field. When embedded in Anisogels for cell culture, cell growth can be directed in three dimensions using mixtures of these pre‐programmed microgel rods.